Health awareness, attitude and practices in male doctors - Nijhawan, Dushyant M.; Upadhye, Aditi Jayant; Upadhye, Jayshree J. (International Journal of Research in Medical Sciences, 2018)
Background: Studies of doctors’ health have emphasised psychological health. Limited data is available on their physical health status. Doctors very often fail to follow recent preventive health guidelines for their physical health. Here, we collected the information available about physical health of male doctors. We stress how important it is for all doctors to have screening and regular check up. Methods: A cross sectional study was conducted among 100 male doctors of M.B.B.S. and higher degrees of various subjects. Selection of male doctors was done randomly. Results: In present study, out of 100 male doctors, 40 (40%) male doctors had normal BMI, 34 (34%) male doctors were overweight, 26 (26%) male doctors were obese while 0 (0%) male doctors were underweight. 89 (89%) had their own blood pressure check up, 88 (88%) had their own blood sugar checked, 85 (85%) had got their own lipid profile done while 85 (85%) male doctors had their electrocardiogram (ECG) done. 29 (29%) male doctors were diagnosed as hypertensive, 10 (10%) were diagnosed as diabetic, 7 (7%) had hyperlipidemia, 4 (4%) as having coronary artery disease, 1 (1%) were detected as collhaving Hodgekin’s Lymphoma. Conclusions: In spite of knowing about all diseases, their complications, screening methods and preventive care, practice of applying screening or preventive methods to themselves is not universal in doctors.